Seismic Scattering Property Changes Correlate With Ground Deformation at Suwanosejima Volcano, Japan. Issue 9 (12th September 2022) - Hirose, Takashi; Ueda, Hideki; Fujita, Eisuke
Abstract: Continuous estimation of changes in seismic velocity and seismic scattering property by passive interferometry using seismic ambient noise is a promising tool for monitoring volcanoes. To improve the usefulness of this method, it is necessary not only to detect subsurface structural changes but also to quantitatively compare the estimated changes in seismic wave velocity and seismic wave scattering property with other observations, such as ground deformation. We applied passive interferometry to continuous seismic records from the Suwanosejima volcano, Japan, recorded between April 2017 and December 2021. We detected repeated significant waveform decorrelations in seismic ambient noise cross‐correlation functions (CCFs), indicating changes in seismic scattering property in the shallow areas of the volcano. These decorrelations were observed from 2 weeks to a few days before the increase in the number of explosions, suggesting that seismic scattering properties changed significantly during that period. We found that the timing of the decorrelation in seismic ambient noise CCFs and tilt changes related to magma accumulation and injection beneath Suwanosejima were well synchronized. The high correlation between the amounts of decorrelation and the tilt change during the magma accumulation period possibly suggests that a large volume of accumulated magma caused great changes in the scattering property. These results provide a significant first step toward a quantitative comparison of the amount of changes in the scattering property with the amount of magma accumulation beneath volcanoes. Plain Language Summary: Continuous estimation of seismic velocity and seismic scattering property changes by passive interferometry using seismic ambient noise is a promising tool for monitoring volcanoes (Brenguier et al., 2008, https://doi.org/10.1038/ngeo104 ; Budi‐Santoso & Lesage, 2016, https://doi.org/10.1093/gji/ggw145 ; Donaldson et al., 2019, https://doi.org/10.1126/sciadv.aax6642 ; Machacca‐Puma et al., 2019, https://doi.org/10.1016/j.jvolgeores.2019.05.014 ; Nishida et al., 2020, https://doi.org/10.1029/2020jb020180 ). Although many previous studies have reported seismic velocity changes related to volcanic activity, only a few of them analyzed the changes in seismic scattering properties beneath volcanoes. We compared the changes in seismic scattering property estimated by passive interferometry and ground deformation obtained from tilt records at Suwanosejima volcano, Japan, between April 2017 and December 2021. This study is the first to investigate the correlation between temporal changes in seismic scattering properties and local ground tilt. We detected repeated significant waveform decorrelations in seismic ambient noise cross‐correlation functions, and these were well synchronized to tilt changes. Moreover, we found a positive correlation between the amounts of waveform decorrelation and the tilt change observed during the magma accumulation and injection periods. These results suggest the possibility of quantitatively comparing the amount of changes in the scattering property inferred from passive interferometry using seismic ambient noise with the amount of magma accumulation beneath volcanoes. Key Points: Waveform decorrelations in seismic ambient noise cross‐correlation functions were detected repeatedly at Suwanosejima volcano, Japan Repeated decorrelations were well‐synchronized with tilt changes that indicate magma accumulation and injection beneath Suwanosejima Comparison of the amounts of decorrelation and tilt change revealed a positive correlation between them